Discovery of inhibitors of MDM2 against nasopharyngeal cancer: an In-Silico Investigation / Juliyan Gunasinghe... [et.al.] - Gunasinghe, Juliyan; Abu Talib, Muhammad Iqbal; Cheah, Stephanie; Runnie Ginjom, Irine; Lee, Sue Han; Chee, Xavier Wezen (2023)
Nasopharyngeal cancer is the fifth most common cancer among males in Malaysia between the ages of 25-59.Epstein-Barr virus is an established cause of nasopharyngeal cancer through an excess upregulation of Murine Double Minute 2 (MDM2). This study investigated potential lead candidates of MDM2 inhibitors by utilizing Molecular Docking and Molecular Dynamics Simulations with the existing drug database, DrugBank. Docking poses were predicted through GOLD molecular docking software utilizing GoldScore, ChemScore, and ChemPLP scoring functions; a consensus scoring was used, achieving an area under the receiver operating characteristic curve of 0.70. The top two compounds with high consensus docking scores, Venetoclax and Phaeophytin-B, were analyzed for binding stability through 250 ns of molecular dynamics simulation.